Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Pada Hoka Hoka Bento Cabang Kelapa Gading - Afanin, Sarah Muthia; Hermawan, Rudianto (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This research aims to determine the effect of the variables Service Quality (X1) and Price (X2) on Customer Satisfaction (Y) at Hoka Hoka Bento Kelapa Gading Branch. Data was collected through questionnaires distributed to 140 respondents and analyzed using IBM SPSS Statistics 27.The results of the analysis show that the average value of the Service Quality and Price variables is 4.32 and 4.28 respectively, which indicates the "Strongly Agree" or "Very good". Analysis was carried out using Correlation Coefficient, Multiple Linear Regression, Coefficient of Determination, as well as Simultaneous Analysis and T Test to measure the influence of the independent variable on the dependent variable. The results of the correlation coefficient analysis show that Service Quality has a strong relationship with Customer Satisfaction (r = 0.835), while Price also shows a strong relationship with Customer Satisfaction (r = 0.777). Multiple linear regression analysis produces the equation Y = 2.534 + 0.535X1 + 0.383X2, indicating that Service Quality and Price positively influence Customer Satisfaction. The test results show that the t-value for Service Quality is 10.037 (p < 0.05) and for Price is 6.473 (p < 0.05), which shows that these two variables have a significant individual effect on Customer Satisfaction. Furthermore, the results of the simultaneous analysis show an F-count value of 238.612 (p < 0.05), which indicates that Service Quality and Price simultaneously have a significant effect on Customer Satisfaction. Analysis of the coefficient of determination shows that Service Quality and Price together explain 76.1% of the variation in Customer Satisfaction. This research strengthens previous findings regarding the importance of Service Quality and Price in influencing.